2009
DOI: 10.1213/ane.0b013e318195bf94
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Skin Temperature for Block Assessment After Infraclavicular Brachial Plexus Block

Abstract: Skin temperature assessment with an infrared thermometer is a reliable, simple and early indicator of a successful nerve block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 9 publications
2
30
2
1
Order By: Relevance
“…12 Skin temperature was found to be a valuable predictor of correct infraclavicular plexus block placement, 13 which is consistent with our results of PI measurements in patients with interscalene nerve blocks. On the other hand, another study in 45 patients showed that the increase in skin temperature occurred very late, after loss of sensory and motor functions in patients with interscalene nerve blocks.…”
Section: Discussionsupporting
confidence: 86%
“…12 Skin temperature was found to be a valuable predictor of correct infraclavicular plexus block placement, 13 which is consistent with our results of PI measurements in patients with interscalene nerve blocks. On the other hand, another study in 45 patients showed that the increase in skin temperature occurred very late, after loss of sensory and motor functions in patients with interscalene nerve blocks.…”
Section: Discussionsupporting
confidence: 86%
“…Previous investigators have demonstrated comparable increases in blood flow 4Y7 and skin temperature 16,17 in the ipsilateral upper extremity after a BPB. The increase in brachial artery blood flow results from both the increase in brachial artery diameter and a decrease in the distal PVR, as evidenced by the increase in V mean and a reduction in the RI, PI, and S/D ratio in this study.…”
Section: Discussionmentioning
confidence: 83%
“…However, despite the observed delay in the increase in skin temperature after the BPB compared with the regional hemodynamic parameters, skin temperature monitoring has been used as an early and objective predictor of the success or failure of a BPB. 16,17 As discussed previously, changes in regional hemodynamic parameters and, in particular, the morphology of the PWD spectral waveform and the increase in EDV occurs sig-nificantly earlier than the temperature change and deserves further investigation as a predictor of success of a BPB.…”
Section: Discussionmentioning
confidence: 88%
“…On closer inspection we found that the nail polish was heat‐sensitive, and had become clear with the increased hand temperature following the onset of sympathetic blockade. As temperature change has been shown to be a reliable early indicator of onset of block , the colour change in our patient's nail polish provided an obvious indication of increased hand temperature and therefore successful onset of block.…”
mentioning
confidence: 56%